Simulation-Based STEM Learning for Vocational High School Students on Wave Rectifiers - Firdaus, Salsabila; Ramadina, Zahra; Claudia, Melinda Amru; Aprial, Muhammad Raifal; Ghaisani, Aliifa Nurfajrina (Current STEAM and Education Research, 2024)
The STEM (Science, Technology, Engineering, and Mathematics) approach significantly enhances practice-based learning in vocational high schools. This study aims to analyze the working principles, performance, and average voltage of three types of rectifiers: half-wave, full-wave center-tapped, and full-wave bridge rectifiers using NI Multisim 13.0 simulation software. Through the STEM approach, students can visualize the working principles of rectifiers, analyze simulation results, and understand the performance differences between each type. The simulation results show that full-wave rectifiers produce more stable DC voltages compared to half-wave rectifiers. This study also provides graphical representations of the input and output waveforms for each type of rectifier, supporting the enhancement of students' critical thinking and technological literacy skills. These findings are expected to serve as relevant teaching materials for STEM-based learning in Vocational High School, particularly in the topic of rectifiers.